Crystal and crystallites structure of natural rubber and synthetic cis-1,4-polyisoprene by a new two dimensional wide angle X-ray diffraction simulation method. I. Strain-induced crystallization - Justin Che (2018)
A novel two-dimensional simulation method to analyze a wide-angle X-ray diffraction (WAXD) pattern is applied to crystal and crystallites of strain-induced crystallization (SIC) of unvulcanized natural rubber (NR) and synthetic polyisoprene rubber (IR) at -50 C. The unit cell dimensions of SIC were determined by calculation of scattering factors based on atomic coordinates and symmetry, and were compared with the observed data. The unit cell dimensions are the same in NR and IR, and do not change during extension. The crystallites' dimensions in NR and IR are almost the same at -50 C. The orientation of crystallites in NR is lower than in IR. The order of crystals in NR is lower than in IR. The crystalline fraction increases with strain because of the increase in the number of crystallites. The onset strain of SIC in NR is smaller than the one in IR. The different behaviors of SIC in NR and IR seem to be caused by the pseudonetwork of NR. © 2013 American Chemical Society.